2010
DOI: 10.1177/0894486510365062
|View full text |Cite
|
Sign up to set email alerts
|

Family Business Succession and Its Impact on Financial Structure and Performance

Abstract: In this article the authors study the impact of a family business transfer on the financial structure and performance based on a sample of 152 small-to medium-sized businesses. The aim is to identify the effects of a succession by relying on panel data gathered over the period 1991 to 2006 resulting in more than 2,000 firm-year observations. The main findings are that a transfer from the first to the second generation negatively influences the debt rate of the company, whereas in successions between later gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
122
2
21

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(151 citation statements)
references
References 73 publications
(82 reference statements)
5
122
2
21
Order By: Relevance
“…Solidity, i.e., leverage measured as equity/total capital, was observed through Affä rsdata, which contains accounting data from the annual report of 2009. It could be expected to be high since family firms tend to prefer control at the expense of profit gained through financial risk (Molly, Laveren, & Deloof, 2010), but solidity could be expected to be inversely correlated with monitoring since it is a proxy for long-term financial stress. Industry was observed through the coding in Affä rsdata, where we identified four major industries and a fifth category including the other corporations.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Solidity, i.e., leverage measured as equity/total capital, was observed through Affä rsdata, which contains accounting data from the annual report of 2009. It could be expected to be high since family firms tend to prefer control at the expense of profit gained through financial risk (Molly, Laveren, & Deloof, 2010), but solidity could be expected to be inversely correlated with monitoring since it is a proxy for long-term financial stress. Industry was observed through the coding in Affä rsdata, where we identified four major industries and a fifth category including the other corporations.…”
Section: Methodsmentioning
confidence: 98%
“…While this is a novel study, falsifying the almost-takenfor-granted idea that family members have advantageous career paths, their study, however, continues the black-boxing of the family, treating all family members as a monolithic group, and disregarding the possibility that kinship characteristics could influence individual family members' career paths differently. Furthermore, it has been found that leverage decreases with the second generation and then increases with the third generation (Molly et al, 2010). One explanation of this is that the second generation tries to preserve the firm, thus reducing financial risk through reducing the leverage.…”
Section: Controlmentioning
confidence: 95%
“…Most studies demand a specific combination of some components of family involvement, although in some cases, they also use firms' self-perception. For instance, Arosa et al (2010), Kotey (2005), and Basco and Pé rez-Rodríguez (2011) chose family ownership and management to identify family firms, whereas Jorissen, Laveren, Martens, and Reheul (2005) and Molly, Laveren, and Deloof (2010) used family ownership and selfperception to classify family firms. Other authors, such as Westhead and Cowling (1997) and Westhead and Howorth (2006), opted to consider succession in addition to family ownership, management and self-perception.…”
Section: Private Family Firms In the Literaturementioning
confidence: 99%
“…Different parameters have been used to define this concept (Astrachan, Klein, & Smyrnios, 2002;Astrachan & Shanker, 2003;Chua et al, 1999), and these firms must necessarily be identified ex-post (Claver, Rienda, & Quer, 2009). Following standard criteria such as ''family participants in business'', which has been used in previous studies (Casillas, Moreno, & Barbero, 2010;Chua et al, 1999;Claver et al, 2009;Molly, Laveren, & Deloof, 2010), we arrived at an operational definition based on two characteristics that firms must manifest to be considered a family business: family members sit on the board or in management posts, and/or the capital is divided among family members. García-Castro and Casasola-Martínez (2011) show that the mere presence of certain components of family involvement (such as family in ownership) is a sufficient condition for the presence of other components.…”
Section: Research Design and Samplementioning
confidence: 99%